BiMnPO5 with ferromagnetic Mn2+–(μ-O)2–Mn2+ units: a model for magnetic exchange in edge-linked Mn2+O6 octahedra. Issue 57 (24th June 2021) - Li, Rukang; Smith, Ronald I.; Greaves, Colin
Abstract : Computations and neutron diffraction experiments are used to analyse the magnetic interactions in discrete pairs of edge-linked Mn(ii )O6 octahedra. Abstract : Magnetic interactions within Mn–(μ-O)2 –Mn pairs are crucial to the function of some essential enzymes and catalysts, but their nature is unclear. Neutron diffraction reveals that similar units in BiMnPO5 show ferromagnetic coupling which has been rationalized by density functional theory modelling and calculations of magnetic exchange energies. The results are important to many solid state and biological systems.